2018
DOI: 10.1177/1352458518767051
|View full text |Cite
|
Sign up to set email alerts
|

Fronto-limbic disconnection in patients with multiple sclerosis and depression

Abstract: Background:The biological mechanism of depression in multiple sclerosis (MS) is not well understood. Based on work in major depressive disorder, fronto-limbic disconnection might be important. Objective: To investigate structural and functional fronto-limbic changes in depressed MS (DMS) and non-depressed MS (nDMS) patients. Methods: In this retrospective study, 22 moderate-to-severe DMS patients (disease duration 8.2 ± 7.7 years), 21 nDMS patients (disease duration 15.3 ± 8.3 years), and 12 healthy controls u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Thus, the current study examined whether social cognitive abilities are related to other domains that are affected by MS, including mood symptomatology. Depression and anxiety are common in MS (Arnett, Barwick, & Beeney, ; Arnett et al ., ; Boeschoten et al ., ; Butler, Matcham, & Chalder, ; Siegert & Abernethy, ), and each are associated with different features of MS. Depression has been associated with neuropathology (Rojas et al ., ; van Geest et al ., ), cognitive problems (Arnett et al ., ; Feinstein, ) and poor social support (Gay, Vrignaud, Garitte, & Meunier, ), while anxiety has been associated with increased disability levels and progressive disease course (Askari et al ., ), comorbid depressive symptoms (Giordano et al ., ; Hartoonian et al ., ) and female gender (Giordano et al ., ; Théaudin, Romero, & Feinstein, ). However, there is still a significant amount of unexplained variance in the prediction of depression and anxiety in MS.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the current study examined whether social cognitive abilities are related to other domains that are affected by MS, including mood symptomatology. Depression and anxiety are common in MS (Arnett, Barwick, & Beeney, ; Arnett et al ., ; Boeschoten et al ., ; Butler, Matcham, & Chalder, ; Siegert & Abernethy, ), and each are associated with different features of MS. Depression has been associated with neuropathology (Rojas et al ., ; van Geest et al ., ), cognitive problems (Arnett et al ., ; Feinstein, ) and poor social support (Gay, Vrignaud, Garitte, & Meunier, ), while anxiety has been associated with increased disability levels and progressive disease course (Askari et al ., ), comorbid depressive symptoms (Giordano et al ., ; Hartoonian et al ., ) and female gender (Giordano et al ., ; Théaudin, Romero, & Feinstein, ). However, there is still a significant amount of unexplained variance in the prediction of depression and anxiety in MS.…”
Section: Introductionmentioning
confidence: 99%
“…Plata-Bello et al found a decrease of amplitude of low-frequency fluctuations (ALFF) in the left inferior frontal gyrus in MS patients, and this area correlated with the gray matter volume of the left inferior parietal lobule (11). van Geest et al found that compared to non-depressed MS patients, depressed MS patients had lower white matter volume ( p < 0.01), decreased fractional anisotropy of the uncinate fasciculus ( p < 0.05), and lower resting-state functional connectivity between the amygdala and the frontal regions ( p < 0.05) (12). Furthermore, the disease duration, fractional anisotropy of the uncinate fasciculus, and the functional connectivity pair could explain 48% of variance in the severity of depression.…”
Section: Introductionmentioning
confidence: 99%
“…In another study performed by van Geest et al [7] on 22 patients with depression and MS, 21 nDMS patients and 12 healthy controls, DMS patients had lower FA than did nDMS patients in the left UF (P = 0.05). These authors also found that DMS patients had lower FA in the left cingulum (P = 0.04) and left UF (P = 0.03) than did healthy controls.…”
Section: Discussionmentioning
confidence: 87%
“…Specific MS pathologies may trigger the onset of depression. In major depressive disorder (MDD), there are several brain abnormalities that have been found, such as frontal and limbic atrophy and decreased FA of the fronto-limbic white matter tracts [7].…”
Section: Introductionmentioning
confidence: 99%